2017
DOI: 10.1111/1742-6723.12820
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic trauma mortality reduced by integrated trauma care

Abstract: Multi-faceted interventions directed at the spectrum of trauma resuscitation from pre-hospital care to definitive surgical management were associated with significant reduction in mortality of patients with severe pelvic injury from 2002 to 2013. This demonstrates the effectiveness of an integrated, inclusive trauma system in achieving improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, computer-aided diagnosis systems can be applied in institutes lacking specialists or can even be used in prehospital settings 34 . Evidence shows that early treatment for hip and pelvic fractures can reduce morbidity and mortality [3][4][5][35][36][37] . Rapid diagnosis is the key to achieving early damage control and providing definite treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, computer-aided diagnosis systems can be applied in institutes lacking specialists or can even be used in prehospital settings 34 . Evidence shows that early treatment for hip and pelvic fractures can reduce morbidity and mortality [3][4][5][35][36][37] . Rapid diagnosis is the key to achieving early damage control and providing definite treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, they evaluated the effectiveness of holistic plans for pelvis trauma patients by comparing the prevalence and reported a change in the mortality figure from 20% to 7.7%. [20] Similarly, a 1-year prospective monocentric study suggested that prevention programs should be directed toward a specific population of men to prevent fractures in young individuals and women to prevent injuries in those above the age of sixty. [21] In Edmonton, a 5-year study evaluated the effectiveness of seatbelt legislation, which showed a reduction in the incidence and severity of AF.…”
Section: Introductionmentioning
confidence: 99%
“…The patient group considered most likely to benefit were those with pelvic fractures and shock. However, since the introduction of pelvic fracture guidelines, the widespread use of pelvic binders and pre‐hospital transfusion of blood on Ambulance Victoria helicopters (but not road ambulances), few of these patients arrived shocked . The impact of sophisticated pre‐hospital shock management for a predominantly blunt trauma cohort was demonstrated by the relatively low incidence, on hospital arrival, of haemodynamic instability among the severely injured, blunt trauma patients in this study.…”
Section: Discussionmentioning
confidence: 74%